The timing of adaptation to high- and low-quality ketogenic diets: a parallel-arm randomized controlled feasibility study - Towsley, Alissa Nicole (Kansas State University, 2022)
Background: With ketogenic diets gaining popularity among individuals who are considered healthy, there is controversy regarding the time necessary for adaptation to this dietary pattern. In addition, little is known about the effects of ketogenic diets on health outcomes in this population. The current study aimed to test the feasibility of short-term, high- (HQKD) and low-quality ketogenic dietary (LQKD) interventions, after both 7–10 days, and four weeks. Methods: Participants (18–35yrs) were recruited and randomized to one of three 4-week interventions: HQKD, LQKD, or a Westernized-dietary pattern control group (CG). One-week (seven days) menus were created, standardized, and repeated over the 4-week intervention period. Dietary quality (DQ) was calculated using the Healthy Eating Index 2015 and was used to differentiate menus (HQKD 76/100, LQKD 45/100). Feasibility outcomes included adherence, dropout, ketone body production, ketogenic induction symptoms, compliance with dietary patterns, and ketogenic diet self-efficacy. In addition, anthropometrics, metabolic assessments, diet adaptation assessments (resting respiratory quotient (RQ), exercise efficiency), physical activity assessments, and dietary intake assessments (ASA-24, 3-day food records) were conducted. Descriptive statistics were determined using SPSS software version 28.0. Results: Participants (n=11) were recruited, completed the screening visit, and passed eligibility criteria. Six participants dropped out (55%). Five participants completed the study (20–34yrs, 73% female, 73% white). No serious adverse events were reported. Total Mood Disturbance increased in HQKD (80.5±3.5 to 90.5±0.7) and LQKD (87±4.2 to 95±0) from week 1 to week 3 and decreased from week 3 to week 7 (HQKD: 87±9.9; LQKD:80±0). Three participants adhered to the 4-week dietary intervention for an average of 26 out of 28 days (94.1%), and the remaining participant adhered only 35.7%. Ketone body levels did not fluctuate for the CG (0–5 mg/dL); however, there was some fluctuation in the ketogenic diet conditions, which reached higher levels in the LQKD (80 mg/dL) as compared to the HQKD (40 mg/dL). Ketogenic induction symptoms included mild-to-severe lightheadedness and moderate muscle weakness (100% HQKD), and mild-to-moderate headaches and difficulty concentrating (100% LQKD). Ketogenic diet participants (n=4, 100%) reported that they were “very sure” they could follow a ketogenic diet the first week; however, at follow up, all ketogenic diet participants (n=4) were “not at all” confident that they could maintain a ketogenic diet as a lifestyle. There were decreases in fasting blood glucose (HQKD: 77.5±19.1 to 69.5±3.5 mg/dL; LQKD: 92.0± 1.4 to 83.5± 2.1 mg/dL) and triglyceride (HQKD: 103.5±48.8 to 90.5±19.1 mg/dL) levels. Conclusions: This small feasibility trial suggested that adaptation to a ketogenic diet may require two to three weeks, with no differences between high-quality and low-quality diets. Due to a small sample size, and the feasibility nature of the current study, hypothesis testing could not be conducted; however, the current results indicate that high dietary quality may be efficacious for cardiometabolic health outcomes, even in healthy individuals. Future fully powered studies that provide pre-determined menu items to participants are warranted to elucidate time requirements for adaptation to ketogenic diets as well as the role of DQ on the cardiometabolic health outcomes when complying with this dietary pattern.
Keywords: Ketogenic diet; Dietary quality; Feasibility; Adaptation; Healthy Eating Index